Do Marked Topics Enhance Memory? - Netz, Hadar; Eviatar, Zohar; Kuzar, Ron (Research in Language, 2011)
We examined the effects of markedness, the deviation from the canonical Subject-Verb-Object structure in English, on the memory of listeners for the topic of the sentence. We used three marked topic constructions: Left-Dislocation, Object-Fronting, and Subject-Marking. Sentences with these structures were inserted as the 6th item in lists of 12 canonical sentences. In all sentences the topic was the name of a man. We measured recall of the critical name. The results revealed that topics of Left-Dislocated sentences were recalled more than topics of the other constructions, with topics of Object-Fronting sentences recalled the least. We briefly discuss how sentence processing procedures might give rise to these effects.